THE ROLE OF DEPRECIATION IN AUDITING FIXED ASSETS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
The depreciation of fixed assets is a vital component of the audit process, influencing financial statements and organizational performance. This article examines the significance of auditing depreciation, detailing the methodologies employed and the challenges faced by auditors in ensuring accurate financial reporting. The study underscores the essential role of depreciation in presenting the true economic value of assets and maintaining financial transparency.